(untitled) (Zaporizhzhia Historical Review, 2021)
The article illustrates the activities of Y. P. Novitsky and D. I. Yavornitsky connected with gathering and scientific fixation of the information upon accidental underwater discoveries in the Dnieper river. The author provides the most remarkable examples of such information extracted from the works of the mentioned scientists. The article underlines the important role of their contribution to the successful development of the underwater hydroarchaelogy of the Dnieper river and near the island Khortytsya in the second part of the XX century and the beginning of the XXI century.